Social Protection Situational Analysis : Albania - World Bank (Washington, DC, 2022)
The objective of this brief situational analysis is to assess the extent to which each element of the social protection system in Albania fulfills its purpose; to determine whether the system as a whole satisfies the four principles outlined in the report; and to identify knowledge gaps and areas for reform in the short, medium and long term, as well as lessons learned from the response to the Coronavirus disease 2019 (COVID-19) pandemic. The analysis finds that Albania has implemented important reforms of the social protection system in the past years to improve the effectiveness and equity in the system. While some of these reforms are beginning to bear fruit, others must be sustained and furthered to achieve the intended results. The situational analysis unfolds as follows: section I gives an introduction; section II reviews the main poverty and labor market outcomes in Albania; section III provides a brief overview of the social protection system in Albania; section IV looks at non-contributory cash transfers to support the poor, the vulnerable and persons with disabilities; section V examines social services; section VI analyzes pensions; section VII explores employment and active labor market programs; section VIII reviews the social protection response to the COVID-19 pandemic; and section XI concludes by identifying main areas for reforms and knowledge gap areas where more detailed assessments will be needed.